Keterampilan Metakognisi Mahasiswa Program Studi Bimbingan Dan Konseling Terhadap Mata Kuliah Statistik - Muya Barida (Program Studi bimbingan Konseling PPs UNM Makassar, 2017)
The purpose of this study to determine metacognition skills possessed by students. The study used phenomenology research model. Subjects of this study are counseling and guidance students who follow the statistical course of the 2010-2014 class. Data were collected by conducting interviews and through qualitative questionnaires. Further data is analyzed by phenomenology analysis technique. The result of the study can be concluded that the student tendency has negative metacognition skills and some students have positive metacognition skills.